Analisis Framing Pemberitaan Kematian Qassem Soleimani di Media Online Hidayatullah.com Periode Januari 2020 - Nafisah Zahra; Rachmad Kriyantono; Bambang Dwi Prasetyo (Universitas Merdeka Malang, 2020)
This study aims to find out how Hidayatullah.com online media constructs news about the death of Qassem Soleimani. The killing of Soleimani carried out by the United States at Baghdad International Airport, Iraq, on January 3, 2020 by an airstrike. This attack heightened the tension between Iran and the United States. This study uses qualitative methods and Robert Entman's framing analysis. The research data are 5 news texts published by Hidayatullah.com during January 2020 which reported about Soleimani's death. This research focuses on the choice of words in reporting about Soleimani which can form certain framing. Based on the analysis that has conducted, there is an emphasis on the figure of Soleimani as someone who played a role in conflicts in Middle Eastern countries, such as Iraq and Syria. Besides highlighting Soleimani's figure as the cause of Middle East conflict, the 5 articles also emphasize the concerns of various parties over a further conflict between Iran and the United States as the result of Soleimani's murder. Keywords: Qassem Soleimani, Framing Analysis, Middle East Conflict